Workforce Empowerment in Digital Innovation Governance in the Management of Regional Own-source Revenue of Makassar City - Arfandi, Muhammad Fuad (KnE Social Sciences, 2025)
Optimal management of regional own-source revenue will encourage better regional development. In the current digitalization era, governance based on digital innovation is a key factor in increasing the amount of regional own-source revenue. Therefore, this study aims to analyze workforce empowerment in digital innovation governance in managing regional own-source revenue. This study uses a qualitative approach with a case study strategy. The research informants are the leaders and staff at the Makassar City Regional Revenue Agency, as the leading sector in regional revenue management. Data sources include primary and secondary data. Data collection through observation, in-depth interviews, and documentation. Data analysis includes data collection, data reduction, data presentation, and drawing conclusions. The results of the study show that the readiness of the Regional Revenue Agency to carry out digital innovation is not optimal. Digital innovations currently used include the PAKINTA application, payment integration with Qris and Virtual Account, electronic regional government transactions (ETPD), and digital socialization and education. From the perspective of human resource empowerment, it shows that the level of digital literacy of the State Civil Apparatus is not evenly distributed. This is also due to the lack of digitalization-based training for operators to manage various digital innovations in the Regional Revenue Agency. The organizational culture is supportive at the top level (top-down), but has not been fully integrated into the daily operational level of ASN. The reward system has not been designed to encourage ASN involvement in digital innovation structurally and systematically. These findings are obstacles in optimizing digital innovation governance in the management of Makassar City’s Regional Original Income (PAD).